2018
DOI: 10.1002/jper.17-0413
|View full text |Cite
|
Sign up to set email alerts
|

Association between the number of teeth and hypertension in a study based on 13,561 participants

Abstract: Findings suggest that a decrease in the number of teeth may be independently associated with hypertension in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 43 publications
0
52
0
1
Order By: Relevance
“…In addition, although tooth loss is a component of the path to complete edentulism, complete edentulism as a construct that may have characteristics and associated factors distinct from general tooth loss. In cross-sectional studies, edentulism has been found to be associated with increased SBP, 6,7 DBP, 7 and prevalent hypertension. 7,14 Edentulism has additionally been found to be associated with coronary heart disease, 11 stroke, 12 and allcause mortality 13 in other cohort studies, and recently with all-cause and CVD mortality risks within the WHI-OS using the same assessment of edentulism as here.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, although tooth loss is a component of the path to complete edentulism, complete edentulism as a construct that may have characteristics and associated factors distinct from general tooth loss. In cross-sectional studies, edentulism has been found to be associated with increased SBP, 6,7 DBP, 7 and prevalent hypertension. 7,14 Edentulism has additionally been found to be associated with coronary heart disease, 11 stroke, 12 and allcause mortality 13 in other cohort studies, and recently with all-cause and CVD mortality risks within the WHI-OS using the same assessment of edentulism as here.…”
Section: Discussionmentioning
confidence: 98%
“…In cross-sectional studies, edentulism has been found to be associated with increased SBP, 6,7 DBP, 7 and prevalent hypertension. 7,14 Edentulism has additionally been found to be associated with coronary heart disease, 11 stroke, 12 and allcause mortality 13 in other cohort studies, and recently with all-cause and CVD mortality risks within the WHI-OS using the same assessment of edentulism as here. 23 Numerous studies have reported significant positive associations between periodontal disease based on selfreport or clinically measured periodontal disease status and hypertension using either cross-sectional or case-control designs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The oral examination was performed by dentists and other medical professionals. Details of the survey design methods and methodological explanations are summarized in several reports …”
Section: Methodsmentioning
confidence: 99%
“…Previous cross-sectional studies suggest a significant association between hypertension and tooth loss in postmenopausal women. 27,28 Alcohol consumption among women was associated with a higher number of teeth present compared with abstainers in the Copenhagen Oral Health Senior Study. 29 However, no such association was found in the study of Ishikawa et al in Japan.…”
Section: Limitationsmentioning
confidence: 99%